FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN GOOD GOVERNANCE (STUDI KASUS OPD KOTA PALEMBANG) - Agustina, Dwi; Periansya; Dwitayanti, Yevi (Jurnal Riset Terapan Akuntansi, 2024)
This study aims to determine and analyze the effect of government accounting systems and the role of APIP on the implementation of good governance (PGG) with quantitative methods. The population in this study was the Regional Apparatus Organization (OPD) which amounted to 32 OPD (using purposive sampling technique). The data collection technique used a questionnaire with respondents consisting of the head of the office at the Palembang City OPD, the head of the finance subdivision, the finance staff, the head of the planning and program subdivision. Data were analyzed using multiple linear regression techniques using SPPS version 29. Based on the results of the study, it is known that the variables of government accounting systems and the role of APIP partially have a positive and significant effect on the implementation of good governance (PGG). Simultaneously, the government accounting system and the role of APIP have a positive and significant effect on the implementation of good governance (PGG). This study concluded that the government accounting system and the role of APIP (Government Internal Supervisory Apparatus) are very influential in the implementation of good governance in the Palembang City OPD. An effective accounting system helps local governments perform their functions well. APIP also plays an important role in conducting internal supervision, supporting the implementation of the principles of good governance implementation. Overall, both have a significant positive impact on the management of Palembang City Government. Keywords: SAP, Role of APIP, PGG